2020
DOI: 10.18517/ijaseit.10.4.12429
|View full text |Cite
|
Sign up to set email alerts
|

Improving Health Care Service through Healthy Psychological Capital and Positive Attitudes

Abstract: This study aims to investigate the interaction between Psychological Capital (PsyCap) and Organizational Commitment in predicting Organizational Citizenship Behaviors (OCB) via Work-Engagement among nurses in Indonesia. Although most studies supported that PsyCap always had a positive impact on desired employee's outcomes, the effect could be different across jobs. The Cognitive Evaluation Theory was used to explain how the coexistence of Organizational Commitment could reduce the effect of Nurse's PsyCap. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
(79 reference statements)
1
12
0
Order By: Relevance
“…Unlike other previous findings in business contexts (Wirawan et al, 2020) and public sectors (Daraba et al, 2021;Saleh et al, 2020;Tamar et al, 2020), this study focused on the direct effect of both leaders' positive characteristics and employees' psychological states on Work Engagement in public organisations. The results confirmed the dominant effect of leadership over employees' positive psychological states.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Unlike other previous findings in business contexts (Wirawan et al, 2020) and public sectors (Daraba et al, 2021;Saleh et al, 2020;Tamar et al, 2020), this study focused on the direct effect of both leaders' positive characteristics and employees' psychological states on Work Engagement in public organisations. The results confirmed the dominant effect of leadership over employees' positive psychological states.…”
Section: Discussionmentioning
confidence: 94%
“…Psychological Capital (PsyCap) is a form of employee's psychological resources (Luthans et al, 2015). To illustrate, PsyCap predicted engagement among front-line staff in the hospitality business (Paek et al, 2015), employees in various large for-profit companies (Chaurasia and Shukla, 2014;Joo et al, 2016;Wirawan et al, 2020), and public services (Saleh et al, 2020). Nevertheless, Kang & Busser (2018) and Parrott et al (2019) postulated that PsyCap and leadership should be employed to predict Work Engagement in different job types (e.g., technician vs. hospitality) and levels (e.g., staff vs. manager).…”
Section: Introductionmentioning
confidence: 99%
“…The next part of the findings concerned the indirect effect of soft skills on career engagement through the role of PsyCap. PsyCap has been known for its tremendous impact on employees' work engagement and performance (Daraba et al , 2021; Joo et al , 2016; Saleh et al , 2020; Tamar et al , 2020; Wirawan et al , 2020). This study confirmed that PsyCap provided resources for students' and employees' career engagement.…”
Section: Discussionmentioning
confidence: 99%
“…psychological resources). Several empirical findings have established that leadership and PsyCap serve as the two primary resources to help people engage in their activities (Avolio and Gardner, 2005; Saleh et al , 2020; Wirawan et al , 2020; Woolley et al , 2011).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation